OP0084 Serum fibroblast growth factor 2 is a useful biomarker to distinguish adult onset still disease from sepsis. (12th June 2018) - Koga, T.; Sumiyoshi, R.; Sato, S.; Migita, K.; Shimizu, T.; Umeda, M.; Nonaka, F.; Fukui, S.; Kawashiri, S.-Y.; Iwamoto, N.; Ichinose, K.; Tamai, M.; et al.
Abstract : Background: The precise cytokine networks in the serum of individuals with adult onset still disease (AOSD) that are associated with its pathogenesis have been unknown. Serum levels of interleukin (IL)−1β, IL-6 and IL-18 have been reported as useful serum biomarkers for diagnosis and disease evaluation among AOSD patients, 1 2 but these cytokines are also elevated in other inflammatory diseases including severe infection. Objectives: We attempted to identify specific biomarkers to distinguish AOSD from sepsis. Methods: We measured serum levels of 45 cytokines in 66 AOSD patients, 17 sepsis patients and 133 age-matched controls by multi-suspension cytokine array. Japan College of Rheumatology-certified rheumatologists diagnosed with AOSD based on the Yamaguchi criteria. Cytokines were ranked by their importance by a multivariate classification algorithm. We performed a logistic regression analysis to determine specific biomarkers for discriminating AOSD from sepsis patients. To identify specific molecular networks, we performed a cluster analysis of each cytokine. Results: Serum fibroblast growth factor 2 ( FGF-2), vascular endothelial growth factor (VEGF), granulocyte-colony stimulating factor (G-CSF), and IL-18 levels were significantly elevated in the AOSD group versus the sepsis group. Multivariate classification algorithms followed by a logistic regression analysis revealed that the measurement FGF-2 distinguished AOSD patients from sepsis patients with the highest accuracy (cut-off value=28.5 pg/mL, sensitivity 100%, specificity 88.2%, accuracy 96.7%). Conclusions: We have demonstrated that FGF-2 can be the best biomarker for differential diagnosis between AOSD and sepsis based on the measurement of multiple cytokines. Although the differential diagnosis between rheumatic diseases and infectious conditions is a great challenge in clinical practice, these findings help to improve the diagnostic performance of AOSD in daily practice. References: [1] Clin Exp Rheumatol. 1996Nov–Dec;14(6):653–5. [2] Rheumatology ( Oxford) 2016Dec;55(12):2237–2247. Disclosure of Interest: None declared